On the redistributive effects of inflation: An international perspective - Paola Boel (Sveriges Riksbank, 2013)
I calibrate the microfounded model in Boel and Camera (2009) to quantify the redistributive effects of inflation for a sample of OECD countries. In doing so, I address two important quantitative issues. First, using harmonized microdata from the Luxembourg Wealth Study, I provide an international comparison of the distribution of households' deposit accounts and financial assets. Second, I account for structural breaks when estimating money demand. I find that several results hold for the countries considered. First, the welfare cost of inflation changes over time, but the direction of the change varies across countries. Second, inflation acts as a regressive tax when a nominal asset other than money is held. Third, the magnitude of the redistributive effects differs across countries and it depends not only on wealth inequality, but also on the curvature and the level of the money demand curve. Last, I show that a subset of the population always prefers an inflationary policy when I extend the model to incorporate a political-economy equilibrium where agents can bargain over the inflation rate.
Keywords: E4; E5; 330; Money; Heterogeneity; Friedman Rule; Welfare Cost of Inflation; Calibration